If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + y(2 + 3y) = 0 4y + (2 * y + 3y * y) = 0 4y + (2y + 3y2) = 0 Combine like terms: 4y + 2y = 6y 6y + 3y2 = 0 Solving 6y + 3y2 = 0 Solving for variable 'y'. Factor out the Greatest Common Factor (GCF), '3y'. 3y(2 + y) = 0 Ignore the factor 3.Subproblem 1
Set the factor 'y' equal to zero and attempt to solve: Simplifying y = 0 Solving y = 0 Move all terms containing y to the left, all other terms to the right. Simplifying y = 0Subproblem 2
Set the factor '(2 + y)' equal to zero and attempt to solve: Simplifying 2 + y = 0 Solving 2 + y = 0 Move all terms containing y to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + y = 0 + -2 Combine like terms: 2 + -2 = 0 0 + y = 0 + -2 y = 0 + -2 Combine like terms: 0 + -2 = -2 y = -2 Simplifying y = -2Solution
y = {0, -2}
| 9(2-1j)+3(5+2j)=2(7-2j)-4(1j-1) | | 3(x+88)= | | 2g+14=-8 | | -4y=6-6x | | 4p-(3p+2r-4)+3-r= | | 4s^2+3s-15=0 | | 17=3 | | 10x-3x+(-5x)= | | 15+5x=5(x+3) | | 8+c=13 | | 4p-(3p+2r-4)= | | 9x^8-72x^6=0 | | v-7=-12 | | 20x-24y=120 | | -4y+2x+8=0 | | x=100-3x | | x-14=-32 | | 0.05x+1.02x= | | 3-2*=11 | | 7+3x=3x+10 | | 19+b=17 | | -q-11=2+4 | | x^4+-15x^2+56=0 | | 2x-3=4x-2 | | 2j+5=6h | | 6a-4a=-36 | | (7x)-(2x)= | | 81=-3(-6+3n) | | 5x+6=10x-94 | | -6y=15-3x | | x=9x+16 | | P(x)=8x-1600 |